Joyful Learning Model Assisted by Smart Apps Creator Improves Elementary School Students' Linguistic Intelligence - Riska Amilia; Putu Aditya Antara (Universitas Pendidikan Ganesha, 2025)
The low linguistic intelligence of third-grade elementary school students remains a problem characterised by limited reading, speaking, and optimal expression of ideas. This condition is influenced by a learning process that tends to be teacher-centred and has not optimised the use of interactive learning media. This study aims to examine and demonstrate the effect of the Joyful Learning model, assisted by Smart Apps Creator, on linguistic intelligence. This study employs a quantitative, quasi-experimental design with a nonequivalent pretest–posttest control group. The research subjects were 68 elementary school students, divided into 34 in the experimental group and 34 in the control group. In comparison, the instrument trial subjects involved 40 fourth-grade students outside the research sample. Data collection was conducted through tests designed to measure students' linguistic intelligence in phonology, morphology, syntax, and semantics. Data were analysed using descriptive statistical techniques to describe data trends and inferential statistics to test the effect of the treatment. The analysis indicates that applying the Joyful Learning model, assisted by Smart Apps Creator, significantly improves the linguistic intelligence of third-grade elementary school students. This research implies that the learning model is effective and suitable for widespread implementation by elementary school teachers to foster interactive, enjoyable learning that strengthens and develops students' language skills.